PENDAPATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI UBI KAYU MANIS DAN UBI KAYU PAHIT DI KECAMATAN SEPUTIH BANYAK KABUPATEN LAMPUNG TENGAH - Anggraesi, Jessica; Ismono, Raden Hanung; Situmorang, Suriaty (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The objectives of this study are to analyze factors affecting production, analyze the percentage of cassava farming income contribution to household income, and analyze the differences income of sweet cassava and bitter cassava farming. This research was conducted in March to April 2018 in Seputih Banyak, Central Lampung. The to determine production factors, the study used Cobb-Douglas production function. To determine contribution of cassava farming income to household income, the study used production analysis, while to determine income of sweet cassava and bitter cassava farming, the study used Independent Sample T-Test. The number of sample for bitter and sweet cassava were 30 respondents each chosen by non-proportional random sampling. The study indicates that the factors affecting production of bitter cassava are NPK fertilizer, urea fertilizer, SP-36 fertilizer, and harvest age, while the factors that significantly influence sweet cassava are land area and NPK fertilizer. The contribution of industrial cassava farming income to household income is 75.01%, while sweet cassava income only accounts for 6.95% of total household income. There is a significant difference between the income of sweet cassava farming and bitter cassava farming. Key words: cassava, income, production